Numerical analysis of an upstream tailings dam - Hassellund, Lovisa; Knutsson, Roger; Mattsson, Hans; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2016)
This paper presents a case study of how the finite element methodcan be utilized to analyze stability of upstream tailings dams. Upstream tailings dams are usually raised gradually and the increased load normallyinfluencesthe stability in an unfavorableway;the load generatesexcess pore water pressures and reduced stability. In this study, an upstream tailings dam in Northern Sweden wasnumericallysimulated with the finite element software PLAXIS 2D in order to assess the stability of the dam. Upstream tailings dams are sensitive to high raising rates since initiated excess pore water pressures might not have time to dissipate. Stability analysis of a tailings damis an application that is very suitable to carry out using finite element software; once a finite element model of thecomplex geometry of adam has been established, it is easy to stepwiseadd new soil volumes, associated with each new raising, to the model.In this case study, it was found that strengthening actions were needed in order to maintain a stable structure. Rockfill berms weregradually added onthe downstream slope of the model to obtaina factor of safety above a recommended value. The volumes of rockfill needed for the berms wereminimized by numerical optimization to reduce costs. The stability betweenthe years2024 and2034 was analyzed; with an annual deposition cycle. The performednumerical studyresulted in a future plan for placement of rockfill berms to establishsufficient stability ofthe tailings dam. It was found that the volume of rockfill in the berms needed, varied during the years studied. Numerical modeling, as presented in this paper, is a useful tool for the dam owner to plan and design for future raisings of a tailings dam